2006
DOI: 10.1364/oe.14.001568
|View full text |Cite
|
Sign up to set email alerts
|

Role of the anomalous self-steepening effect in modulation instability in negative-index material

Abstract: In negative-index materials (NIMs), the self-steepening (SS) effect is proven to be anomalous in two aspects: First, it can be either positive or negative, with the zero SS point determined by the size of split-ring resonator circuit elements. Second, the negative SS parameter can have a very large value compared to an ordinary positive-index material. We present a theoretical investigation on modulation instability (MI) to identify the role of the anomalous SS effect in NIM. We find that the first anomaly of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 20 publications
3
58
0
Order By: Relevance
“…In the simulations presented later in this section the parameters that are considered are self-steepening and the use of a range of magnetooptic parameters that are used to adjust the effect of self-steepening in the metamaterial. It should be noted that the self-steepening coefficient S in equation (6.1) involves very specific properties of the metamaterials which has been pointed out by previous authors [12,122] however here the self-steepening term is that laid out in equation (2.21) of [120] which is arrived at via a different approach and the result is less restrictive than other approximations.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…In the simulations presented later in this section the parameters that are considered are self-steepening and the use of a range of magnetooptic parameters that are used to adjust the effect of self-steepening in the metamaterial. It should be noted that the self-steepening coefficient S in equation (6.1) involves very specific properties of the metamaterials which has been pointed out by previous authors [12,122] however here the self-steepening term is that laid out in equation (2.21) of [120] which is arrived at via a different approach and the result is less restrictive than other approximations.…”
mentioning
confidence: 84%
“…For example, it soon becomes apparent that the sign of the self-steepening [12] parameter can be changed through frequency management. This has a dramatic impact upon modulation instability (MI) and short pulse propagation [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…This model equation has studied for five forms of nonlinear media by the aid of ansatz method (5,29), travelling wave hypothesis (33) as well as mapping methods (22) and collective variables approach (28). This paper will employ the travelling wave hypothesis to secure solutions to the model (1) that is with polynomial law non-linearity.…”
Section: Governing Modelmentioning
confidence: 99%
“…However it is always a challenge to compensate for the loss when engineering these types of waveguides using metamaterials. The theoretical results showed that metamaterials enhance nonlinearity by confining electrical field in a small region that allows more light-matter interaction [11,17,19,20]. In metamaterials, linear and nonlinear coefficients of the propagation equation can be tuned to achieve any combination of signs that is not possible in regular materials.…”
Section: Introductionmentioning
confidence: 99%